2023
DOI: 10.1097/j.pain.0000000000002884
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in pain expressed by patients across diverse disease states: individual patient data meta-analysis of 33,957 participants in 10 randomized controlled trials

Abstract: The experience of pain is determined by many factors and has a significant impact on quality of life. This study aimed to determine sex differences in pain prevalence and intensity reported by participants with diverse disease states in several large international clinical trials. Individual participant data meta-analysis was conducted using EuroQol-5 Dimension (EQ-5D) questionnaire pain data from randomised controlled trials published between January 2000 and January 2020 and undertaken by investigators at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 73 publications
(146 reference statements)
1
4
0
Order By: Relevance
“…We have previously noted that CFA inflammatory pain in males and females differed in response to afferent activity manipulation; female inflammatory pain appears to have more of a central component 52 . This data corroborates those findings and is consistent with the sex differences in pain observed in humans 53,54 .…”
Section: Discussionsupporting
confidence: 93%
“…We have previously noted that CFA inflammatory pain in males and females differed in response to afferent activity manipulation; female inflammatory pain appears to have more of a central component 52 . This data corroborates those findings and is consistent with the sex differences in pain observed in humans 53,54 .…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, future management of post-COVID pain should be applied from a sex perspective considering biological and psychological differences. 18…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, future management of post-COVID pain should be applied from a sex perspective considering biological and psychological differences. 18 Previous history of painful conditions was another factor associated with a higher risk of developing post-COVID pain. We found that up to 40% of our sample experienced pain symptoms before SARS-CoV-2 infection.…”
Section: Post-covid Pain-associated Risk Factorsmentioning
confidence: 99%
“…Sex differences in pain studies are now well established. Evidence indicates that women are more likely to suffer from chronic pain [ 22 ] and report higher pain levels than men across diverse diseases, ages, and geographical regions [ 23 ]. Although the mechanisms underlying these sex differences are not fully understood, recent studies have revealed a sex-specific involvement of different genes, proteins, hormones, and cellular responses with distinct effects on immune function, influencing pain signalling [ 24 ].…”
Section: Introductionmentioning
confidence: 99%